Salivary Gland Pathology in IgG4-Related Disease: A Comprehensive Review - Ilaria Puxeddu; Riccardo Capecchi; Filippo Carta; Antonio Gaetano Tavoni; Paola Migliorini; Roberto Puxeddu (Journal of Immunology Research)
IgG4-related disease (IgG4-RD) is a rare fibroinflammatory condition that can affect almost any organ, characterized by swollen lesions and often by eosinophilia and elevated serum IgG4 concentrations. The diagnosis of IgG4-RD is a challenging task: in fact, single or multiple organs can be affected and clinical, serological, and histological findings can be heterogeneous. In IgG4-RD, the involvement of salivary glands is observed in 27% to 53% of patients. Several organ-specific conditions, now recognized as different manifestations of IgG4-related sialadenitis (IgG4-RS), were viewed in the past as individual disease entities. The study of salivary glands may sometimes be complex, because of the number of pathological conditions that may affect them, often with overlapping clinical pictures. Integration of different imaging techniques is often required in the case of swelling of salivary glands, even though biopsy remains the gold standard for a definite diagnosis of IgG4-RS. Thus, in this review, we discuss new insights in the pathogenesis of IgG4-RD, focusing on its clinical aspects and the tools that are currently available for a correct differential diagnosis when the salivary glands are involved.